Quand l’expérience « spirituelle » s’éprouve par et dans le corps : Pédagogie somatique et transformation identitaire dans le Morbihan - Dansac, Yael (Anthropologica, 2023)
In Morbihan, a department in the French region of Brittany, there are many “self ” discovery practices involving the local megaliths. The schemes offered by these practices are thought to allow the practitioner to develop new relationships between the “self and self” and the “self and the other” by using their body and senses as factors essential to a personal transformation. At the heart of these practices, participants are invited to engage in a sensorial learning journey and cultivate their bodily attention by concentrating on their body and their sensations when they approach the megaliths and touch them. In this article, I analyze the somatic learning and personal transformation processes at the heart of these practices. More precisely, I focus on the three elements that account for the effectiveness of the practices and build the experience of the participants : the progressive learning of a sensorial language, the interpretation of somatic imagery, and the execution of bodily techniques. My theoretical reflections on these elements highlight the mechanisms that make these practices a continuum where “spiritual” experiences manifest as somatic experiences.